Architecture is the Art of Creating Space: Nad knihou Christophera Daye Duch a místo - Cílek, Václav (Lidé města, 2007)
To our ancestors landscape was not only subject of special respect but also of ongoing struggle. Construction of localities, kind of focal points or bases for other incursions, was inherent in the inner or even spiritual colonization of nature. They include cloisters, chapels, Stations of the Cross, important crossroads, and "open spaces" located in front of a bridge or a footbridge. Today, at a time when we have seemingly conquered the nature, we rather perceive nature's nostalgic charge of the past than its distressful or tragic dimension. However, there are some places that are dehumanized, for various reasons - decaying industrial zones, Sudetenland or in modern times hypermarkets, places where we strongly feel need of some reconciliation, fulfillment or neutralization of its genius loci. I am convinced that it is important to realize not only the power and coherence of tradition, but also its troublesome restrain given primarily by everyday petty struggle for bread. That is exactly the kind of struggle that would get down a modern creative person completely.